Micro-entrepreneurs’ competency in Malaysia: Roles of self efficacy - Wee, Melissa; Nuralina Bustamam; Mohd Zaki Sadik; Noraznira Abd Razak; Najihah Hanisah Marmaya; Juan Rizal Sa’ari (Human Resource Management Academic Research Society (HRMARS), 2022)
The research is to identify the roles of self-efficacy that influence micro-entrepreneur’s competency in Malaysia. This study investigates the relationship between marketing, innovation, management and risk-taking towards micro-entrepreneur’s competency. Causal research and a non-probability sampling were applied, specifically judgmental purposive sampling. Primary data was collected through questionnaires that have been distributed among micro-entrepreneurs in Malaysia. 100 respondents were derived from this study by using Statistical Package for Social Science (SPSS). Management and risk-taking were found to be significantly positive meanwhile marketing and innovation were found trivial for this study. This research sees the importance of emphasizing on the elements of management and risktaking in order to enhance the competency of micro-entrepreneur in Malaysia.